2017
DOI: 10.1111/rode.12310
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Early Life Extreme Precipitation Shocks on Short‐term Health and Adulthood Welfare Outcomes

Abstract: This paper examines the impact of exposure to early life rainfall shock on children's anthropometric growth status and other welfare outcomes. The study exploits World Bank repeated cross-section household data on Malawi and exogenous variation in precipitation measures across localities to identify the impact of drought and flood shocks on health, schooling and satisfaction levels. Our main estimate for children's anthropometric growth reveals that an incidence of drought shock leads to a resultant average de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…In India, drought exposure in utero through age 4 is negatively associated with having ever enrolled in school (29) and, in Indonesia, greater rainfall during the year of birth is positively associated with women's educational attainment in adulthood (30). In Malawi, in utero exposure to drought is associated with delayed school entry among male children (31). Further, in rural Ethiopia, greater rainfall during the main agricultural season in early childhood is positively associated with having completed at least 1 y of schooling as well as with attending school at the time of the survey (32).…”
mentioning
confidence: 99%
“…In India, drought exposure in utero through age 4 is negatively associated with having ever enrolled in school (29) and, in Indonesia, greater rainfall during the year of birth is positively associated with women's educational attainment in adulthood (30). In Malawi, in utero exposure to drought is associated with delayed school entry among male children (31). Further, in rural Ethiopia, greater rainfall during the main agricultural season in early childhood is positively associated with having completed at least 1 y of schooling as well as with attending school at the time of the survey (32).…”
mentioning
confidence: 99%
“…The economic shocks associated with drought, especially in terms of seasonal poverty, can impact investment in human capital, including education 56 , 98 , 99 and access to adequate health care. Previous ART adherence studies showed that HIV-positive individuals who had to bear the cost of treatment, including those linked to transportation to clinics, reported poor adherence.…”
Section: Resultsmentioning
confidence: 99%
“…The economic shocks associated with drought, especially in terms of seasonal poverty, can impact investment in human capital, including education, 45,104,108 and access to adequate health care. Previous ART adherence studies showed that HIV-positive individuals who had to bear the cost of treatment, including those linked to transportation to clinics, reported poor adherence 31 .…”
Section: Results: a Systems Understanding Of The Sensitivity Of Art Amentioning
confidence: 99%
“…Drought aggravates the physical and mental health pressures that individuals face. 46,8,47,57,59,102,104,105,127 Like other environmental stressors and extreme events, including floods, drought is linked to disease outbreaks such as Rift Valley Fever, Konzo disease, trachoma, diseases linked to poor hygiene and access to water like diarrhoea, and those carried by vectors like chikungunya outbreaks in East Africa. 46,59 Further, drought has been linked to later life disability, especially among males who also are at risk of both physical and mental disabilities having experienced drought as infants 105 …”
Section: Results: a Systems Understanding Of The Sensitivity Of Art Amentioning
confidence: 99%